Puppies Love - Russell, Rachel Renee (UK, 2015)
Fuzzy friends needs help taking care of a little of puppies. So Nikki volunteers to take them home. Just one problem - she has to hide them from her parents! How hard can it be to sneak seven pups home?...
Keywords: Animal / Pets; Friendship; Juvenile Fiction; Pets sitting